2022
DOI: 10.1097/rlu.0000000000004414
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal Cyst Mimicking Thyroid Cancer Metastasis

Abstract: A 26-year-old woman with pulmonary metastasis of thyroid cancer underwent a total thyroidectomy and cervical lymph node dissection followed by 2 courses of 131 I therapy. The posttherapeutic whole-body scan after the second dose of 131 I therapy showed diffuse tracer uptake in both lungs. Besides this, there is a local abnormal radiotracer uptake in the left axillary region. SPECT/CT images localized this abnormal radioactivity in a subcutaneous, oval-shaped, approximately 2.2-cm slightly hyperdense lesion, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…Similar mechanism, that is, prolonged retention of 131 I in the tears behind a cyst obstructing their normal drainage, was postulated to cause increased radioiodine accumulation inside eye chambers in the single case reported of conjunctival epithelial inclusion cyst associated with orbital radioiodine uptake in a patient with thyroid cancer 6 . However, as in our case we demonstrated 131 I uptake within the cyst, we considered other possible mechanisms of increased radioiodine accumulation, which was also demonstrated in cysts of the liver, sebaceous glands, larynx, thymus, and kidneys and pleuropericardial, bronchogenic, epidermal, and nabothian cysts 7–14 . The exact mechanism of the 131 I accumulation in cysts remains unclear.…”
supporting
confidence: 66%
See 1 more Smart Citation
“…Similar mechanism, that is, prolonged retention of 131 I in the tears behind a cyst obstructing their normal drainage, was postulated to cause increased radioiodine accumulation inside eye chambers in the single case reported of conjunctival epithelial inclusion cyst associated with orbital radioiodine uptake in a patient with thyroid cancer 6 . However, as in our case we demonstrated 131 I uptake within the cyst, we considered other possible mechanisms of increased radioiodine accumulation, which was also demonstrated in cysts of the liver, sebaceous glands, larynx, thymus, and kidneys and pleuropericardial, bronchogenic, epidermal, and nabothian cysts 7–14 . The exact mechanism of the 131 I accumulation in cysts remains unclear.…”
supporting
confidence: 66%
“…6 However, as in our case we demonstrated 131 I uptake within the cyst, we considered other possible mechanisms of increased radioiodine accumulation, which was also demonstrated in cysts of the liver, sebaceous glands, larynx, thymus, and kidneys and pleuropericardial, bronchogenic, epidermal, and nabothian cysts. [7][8][9][10][11][12][13][14] The exact mechanism of the 131 I accumulation in cysts remains unclear. It was suggested that a slow exchange of cyst contents with their environment may cause longer retention of 131 I within a cyst than in extracellular space, which is cleared faster because of urinary excretion of iodine.…”
mentioning
confidence: 99%
“…After 6 years of clinic follow-up, the serum Tg remains <1.0 μg/L, and she remains asymptomatic and free of disease recurrence. 131 I accumulation in cysts has been reported in the literature involving many sites such as epithelial conjunctival inclusion cyst, 1 epidermal cyst, 2 thymus, 3–6 thyroglossal duct, 5 bronchogenic cyst, 4,5,7,8 breast, 5,7 liver, 4,5 hepatic hydatid cyst, 7 renal, 4,5,7,9 ovary, 4,5,9 bone, 9 uterine menstruation dermoid cyst, 9 pleuropericardial, 4,5 sebaceous cyst, 4,5,7 nasolacrimal duct, 4,5 laryngeal cyst, 4 gastrointestinal duplication cyst, 4 nabothian cyst, 4,10 and pancreatic lymphoepithelial cyst 11 . The postulated mechanism of 131 I uptake in the cysts varies and includes incomplete active transport or passive diffusion of the chemical materials and 131 I between the cyst and adjacent tissue followed by its retention within the cystic structure, 5,10–12 chronic inflammation resulting in hypervascularity and increased capillary permeability, 13,14 expression of sodium-iodide symporter in the cystic epithelial cells, 13,15 and organification of 131 I in leukocytes 14 .…”
mentioning
confidence: 99%